Rotationally symmetric formulation of the wave propagation method-application to the straylight analysis of diffractive lenses - Schmidt, S.; Thiele, S.; Herkommer, A.; Tuennermann, A.; Gross, Herbert (Optics Letters, 2017)
We introduce a modified formulation of the wave propagation method for the efficient simulation of rotationally symmetric micro-optical components. The reformulated algorithm provides an increased computational performance of approximately two orders of magnitude and strongly reduced memory requirements, in comparison to the original formulation. This enables the efficient wave optical simulation of extended micro-optical structures beyond the common thin-element approximation. As a prototypical example, we assess the modified algorithm for the evaluation of straylight induced by diffractive lenses. We find an excellent accuracy, while comparing to rigorous simulations, which justifies the ability to overcome the limitations of the thin-element approximation.
CRIS-Team Scopus Importer:2023-04-20